Preparation method and application of bi-component catalyst

Through the preparation method of two-component catalysts, urea precipitation method and vacuum impregnation method, the problems of complexity and selective regulation of catalysts in the production of 1,2-propylene glycol in biomass resources are solved, and low-cost and high-efficiency are achieved 1,2-propylene glycol production has good catalytic activity and stability.

CN119303581APending Publication Date: 2025-01-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411356602.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When using biomass resources to produce 1,2-propylene glycol, the catalyst system is complex, selective regulation is difficult, and the cost is high, making it difficult to achieve efficient and low-cost industrial production.

Method used

The two-component catalyst preparation method is adopted to prepare the catalyst by urea precipitation method, vacuum impregnation method or co-precipitation method, using nickel elements as active components and transition metal elements as auxiliary metal components, combined with alkaline support, achieving one-step high selectivity Catalytic conversion of sugar to 1,2-propanediol.

Benefits of technology

It realizes the production of 1,2-propylene glycol with simple operation and good atomic economy. It has low catalyst cost and is suitable for industrial applications. It also shows excellent catalytic activity and stability. It is suitable for different sugar substrates and has good substrate adaptation. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303581A_ABST
    Figure CN119303581A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a bi-component catalyst, and belongs to the technical field of energy and chemical industry. Comprising the following steps: S1, introducing an active component into an alkaline carrier through a urea precipitation method to obtain a bi-component catalyst precursor A; s2, introducing a co-metal component into the bi-component catalyst precursor A through a vacuum impregnation method or a coprecipitation method to obtain a bi-component catalyst precursor B; and S3, roasting the bi-component catalyst precursor B, and performing reduction activation to obtain the bi-component catalyst. Various types of sugars can be catalytically converted into 1, 2-propylene glycol in a one-step high-selectivity manner. According to the bi-component catalyst, various kinds of sugars can be used as reaction raw materials, one-step high-selectivity catalytic conversion is performed on the catalyst to obtain 1, 2-propylene glycol, and good substrate adaptability is achieved for different sugar substrates. The reaction process is simple to operate, the atom economy is good, and the catalyst is simple and feasible to prepare, low in cost and easy to industrially amplify.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of a two-component catalyst, and belongs to the technical field of energy chemical industry. Background Art

[0002] With the increasing shortage of fossil resources and the serious greenhouse effect caused by large-scale carbon dioxide emissions, the development of renewable biomass resources as raw materials to synthesize bulk chemicals has become an urgent and realistic need. 1,2-propylene glycol is an important organic chemical raw material. It is not only an important monomer for unsaturated polyesters, epoxy resins, alkyd resins and other polyesters, but also has a wide range of applications in flavors and fragrances, cosmetics, medicine, tobacco and other fields. At present, the mainstream production process of 1,2-propylene glycol is the direct hydration of propylene oxide using petroleum as raw material, which faces the limitations of long process flow, large investment and high energy consumption.

[0003] The production of 1,2-propylene glycol from biomass resources can be divided into two routes: fermentation and catalytic conversion. The former uses genetic engineering to construct active strains to convert raw materials such as glucose, lactic acid, and glycerol into 1,2-propylene glycol in the liquid phase, but the target product concentration in the fermentation broth is low, the fermentation operation process is numerous, and the separation process is complex, so the economic efficiency is poor (Applied and Environmental Microbiology, 1999, 65 (3): 1180-1185.). In contrast, the liquid phase hydrogenation reaction route is used to efficiently catalyze the conversion of raw materials such as glucose and glycerol into 1,2-propylene glycol. Since the oxygen atoms in the raw material molecules can be retained to the maximum extent, this route has good atom economy.

[0004] Shell reported a dual-catalyst reaction system containing a tungsten-based retro-aldol catalytic substance and an alkali metal-containing substance, which catalyzed the conversion of glucose into a mixture of polyols including ethylene glycol, propylene glycol, mannitol, etc. (PCT / EP2017 / 069568). Tongji University reported a core-shell structured Pt / deAl-Beta@Mg(OH)2 catalyst that converted sucrose into propylene glycol with a yield of more than 32% (CN115636720). Nanjing University of Technology reported a γ-Al2O3-loaded nickel-based catalyst for catalyzing the selective cracking of sugars and sugar alcohols into low-carbon alcohols, mainly ethylene glycol, 1,2-propylene glycol, and 1,3-propylene glycol (CN104557451). Dalian University of Technology has developed a two-stage intermittent reaction method, using CuNi / MgO catalyst to first catalyze the hydrogenolysis / hydrogenation reaction of glucose aqueous solution at low temperature to generate intermediates, and then heating the intermediates to further convert them into low-carbon polyols mainly composed of 1,2-propylene glycol (CN104961625). The Dalian Institute of Chemical Physics of the Chinese Academy of Sciences has developed a Mg-containing hydrotalcite-based catalyst suitable for converting high-concentration sugars to 1,2-propylene glycol (CN110711588).

[0005] Some of the above catalytic systems use homogeneous additives or multi-step catalytic processes, which increases the complexity of the system. In addition, the selective regulation of 1,2-propylene glycol is still a difficult problem to solve, and obtaining a high yield of 1,2-propylene glycol in a single catalyst system is still a major challenge. Summary of the invention

[0006] The purpose of this application is to provide a preparation method and application of a two-component catalyst, which can use various types of sugars as reaction raw materials, and can be highly selectively catalyzed and converted into 1,2-propylene glycol in one step on the catalyst, and has good substrate adaptability for different sugar substrates. The reaction process is simple to operate, with good atom economy, and the catalyst preparation is simple and easy, low cost, and easy to scale up industrially.

[0007] According to one aspect of the present application, a method for preparing a two-component catalyst is provided, comprising the following steps:

[0008] S1: introducing the active component into the alkaline support by urea precipitation method to obtain a two-component catalyst precursor A;

[0009] S2: introducing the co-metal component into the dual-component catalyst precursor A by vacuum impregnation or co-precipitation to obtain a dual-component catalyst precursor B;

[0010] S3: calcining the dual-component catalyst precursor B, reducing and activating it, to obtain the dual-component catalyst;

[0011] The alkaline carrier is selected from at least one of alkaline silica gel, alkaline alumina, magnesium oxide, zinc oxide, and magnesium aluminum spinel;

[0012] The active component includes nickel element;

[0013] The auxiliary metal component is selected from at least one of transition metal elements and lanthanide elements;

[0014] The transition metal element is selected from at least one of zirconium, ruthenium, cobalt, iron, platinum and palladium;

[0015] The lanthanide element is selected from at least one of cerium and lanthanum.

[0016] Preferably, the alkaline carrier is selected from at least one of basic alumina and magnesium aluminate spinel.

[0017] Optionally, the content of the active component in the dual-component catalyst is 5 to 40 wt%.

[0018] Optionally, the content of active components in the two-component catalyst is independently selected from any value of 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or a range between any two of the above points.

[0019] Optionally, the content of the co-metal component in the dual-component catalyst is 0.1 to 4 wt%.

[0020] Optionally, the content of the co-metal component in the dual-component catalyst is independently selected from any value of 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt% or a range between any two of the above points.

[0021] Optionally, in step S1, the step of preparing the two-component catalyst precursor A by urea precipitation method is: mixing the alkaline carrier, water, nickel salt and urea, stirring and aging, placing the obtained mixture in a container with a reflux device, heat-insulating treatment, and drying I to obtain the two-component catalyst precursor A.

[0022] Optionally, the mass ratio of the alkaline carrier, water, nickel salt and urea is alkaline carrier: water: nickel salt: urea = 1: 25-150: 0.06-2.4: 0.1-9.5.

[0023] Preferably, the mass ratio of the alkaline carrier, water, nickel salt and urea is alkaline carrier: water: nickel salt: urea = 1: 25-100: 0.4-2.0: 2.0-9.5.

[0024] Further preferably, the mass ratio of the alkaline carrier, water, nickel salt and urea is alkaline carrier: water: nickel salt: urea = 1: 25-80: 0.6-2.0: 2.6-9.0.

[0025] Optionally, the nickel salt is selected from at least one of nickel nitrate, nickel oxalate, nickel chloride, nickel acetate, nickel sulfate and nickel carbonate.

[0026] Optionally, the stirring aging temperature is 15-25°C.

[0027] Optionally, the stirring speed of the stirring aging is 150 to 10000 rpm.

[0028] Optionally, the stirring aging time is 2 to 24 hours.

[0029] Optionally, the temperature of the heat preservation treatment is 75-100°C.

[0030] Optionally, the insulation treatment time is 12 to 72 hours.

[0031] Optionally, the temperature of the drying I is 80-150°C.

[0032] Optionally, the drying time I is 1 to 48 hours.

[0033] Optionally, in step S2, the steps of preparing the two-component catalyst precursor B by vacuum impregnation method are: dissolving the auxiliary metal salt in water to obtain the auxiliary metal salt solution, mixing the auxiliary metal salt solution with the two-component catalyst precursor A, impregnating equal volumes, and drying Ⅱ to obtain the two-component catalyst precursor B.

[0034] Optionally, the temperature of the equal volume impregnation is 15-25°C.

[0035] Optionally, the pressure of the equal volume impregnation is ≤10Pa.

[0036] Optionally, the equal volume immersion time is 2 to 24 hours.

[0037] Optionally, the temperature of the drying II is 70-150°C.

[0038] Optionally, the drying II takes 1 to 48 hours.

[0039] Optionally, in step S2, the steps of preparing the two-component catalyst precursor B by co-precipitation method are: dissolving the auxiliary metal salt in water to obtain the auxiliary metal salt solution, adding the two-component catalyst precursor A to obtain a mixture C; dissolving the precipitant in water to obtain a solution D; adding the solution D to the mixture C under stirring conditions until the pH value is 6 to 8, aging, and drying III to obtain the two-component catalyst precursor B.

[0040] Optionally, the mass ratio of the two-component catalyst precursor A to the auxiliary metal salt is 1:0.001-0.2.

[0041] Optionally, the precipitant is selected from at least one of ammonia water, sodium carbonate, sodium bicarbonate and ammonium carbonate.

[0042] Optionally, the mass content of the precipitant in the solution D is 0.5-16 wt %.

[0043] Optionally, the aging temperature is 20-75°C.

[0044] Optionally, the aging time is 2 to 36 hours.

[0045] Optionally, the temperature of the drying III is 70-150°C.

[0046] Optionally, the drying time of III is 1 to 48 hours.

[0047] Optionally, the auxiliary metal salt is selected from at least one of cerium nitrate, lanthanum nitrate, zirconium oxynitrate, ruthenium chloride, cobalt nitrate, iron nitrate, chloroplatinic acid, and chloropalladic acid.

[0048] Optionally, in step S3, the calcination temperature is 350-700°C.

[0049] Optionally, the calcination time is 2 to 48 hours.

[0050] Optionally, the reducing gas for reduction activation is selected from at least one of hydrogen and methane.

[0051] Optionally, the reduction activation temperature is 200-600°C.

[0052] Optionally, the reduction activation time is 0.5 to 24 hours.

[0053] As a specific implementation, the method for preparing the dual-component catalyst includes the following steps.

[0054] In step S1, the steps of preparing the dual-component catalyst precursor A by urea precipitation method are:

[0055] (1) placing an alkaline carrier, deionized water, nickel salt, and urea in a sealed container in sequence to obtain a mixture having the following mass ratio: alkaline carrier: deionized water: nickel salt: urea = 1:25-150:0.06-2.4:0.1-9.5, and stirring and aging for 2-24 hours;

[0056] (2) placing the mixture in a container with a reflux device, heating it to 75-100° C. for 12-72 hours, and then cooling it naturally to room temperature;

[0057] (3) Filtering and washing the mixture, and drying it at 80 to 150° C. for 1 to 48 hours to obtain the nickel-containing dual-component catalyst precursor A.

[0058] In step S2, the steps of preparing the dual-component catalyst precursor B by vacuum impregnation are:

[0059] (1) dissolving a metal salt in deionized water and stirring to obtain a metal salt solution;

[0060] (2) impregnating the auxiliary metal salt solution into the nickel-containing dual-component catalyst precursor A by equal volume impregnation at a pressure not higher than 10 Pa, and standing at room temperature for 2 to 24 hours after being fully mixed;

[0061] (3) Drying the mixture at 70-150° C. for 1-48 hours to obtain the catalyst precursor B containing two components.

[0062] In step S2, the steps of preparing the dual-component catalyst precursor B by coprecipitation method are:

[0063] (1) dissolving a metal salt in deionized water, adding a two-component catalyst precursor A, and stirring to obtain a mixture C;

[0064] (2) dissolving the precipitant in water and stirring to obtain solution D;

[0065] (3) adding solution D to mixture C under stirring until the final pH is 6-8, and aging at 20-75° C. for 2-36 h;

[0066] (4) Filtering and washing the mixture, and drying it at 70 to 150° C. for 1 to 48 hours to obtain the catalyst precursor B containing two components.

[0067] According to another aspect of the present application, there is provided an application of a two-component catalyst prepared by the above-mentioned preparation method in catalyzing the conversion of a sugar solution into 1,2-propylene glycol, comprising the following steps: adding the two-component catalyst, water and sugar into a reaction kettle, sealing it, replacing it with a hydrogen atmosphere, reacting, and obtaining a product.

[0068] Optionally, the mass ratio of the two-component catalyst, water and sugar is 1:20-5000:0.2-500.

[0069] Optionally, the mass ratio of the two-component catalyst to water is independently selected from any ratio of 1:20, 1:50, 1:100, 1:200, 1:500, 1:1000, 1:2000, 1:2500, 1:3000, 1:4000, 1:5000 or a range between any two of the above ratios.

[0070] Optionally, the mass ratio of the two-component catalyst to the sugar is independently selected from any ratio of 1:0.2, 1:0.5, 1:1, 1:5, 1:10, 1:50, 1:100, 1:200, 1:250, 1:300, 1:400, 1:500 or a range between any two of the above ratios.

[0071] Optionally, the sugar is selected from at least one of monosaccharides, disaccharides and polysaccharides.

[0072] Optionally, the monosaccharide is selected from at least one of glucose, fructose and xylose.

[0073] Optionally, the disaccharide is selected from at least one of maltose, sucrose, lactose and cellobiose.

[0074] Optionally, the polysaccharide is selected from at least one of fructooligosaccharides, xylooligosaccharides, starch, straw sugar, and nanocellulose.

[0075] Optionally, the reaction pressure is 1.5-16 MPa.

[0076] Optionally, the reaction pressure is independently selected from any value among 1.5MPa, 2MPa, 4MPa, 6MPa, 8MPa, 10MPa, 12MPa, 14MPa, 16MPa or a range between any two of the above points.

[0077] Optionally, the reaction temperature is 190-250°C.

[0078] Optionally, the reaction temperature is independently selected from any value of 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C or a range between any two of the above points.

[0079] Optionally, the reaction time is 0.2 to 12 hours.

[0080] Optionally, the reaction time is independently selected from any value among 0.2h, 0.5h, 1h, 2h, 4h, 6h, 8h, 10h, 12h or a range between any two of the above points.

[0081] As a specific embodiment, a two-component catalyst prepared by the above preparation method or the above-mentioned two-component catalyst is provided for catalyzing the reaction of converting a sugar solution into 1,2-propylene glycol, wherein sugar is used as a raw material and a hydrogenation cracking reaction is carried out in an autoclave reactor under a hydrogen atmosphere.

[0082] The reaction steps include: adding the two-component catalyst, deionized water and sugar into a reactor, sealing the reactor, replacing the atmosphere of the reactor with a hydrogen atmosphere, stirring, heating until the temperature and hydrogen pressure reach a specified level, and reacting for a period of time.

[0083] Optionally, the stirring speed is 120 to 3000 rpm.

[0084] The beneficial effects of this application include:

[0085] 1) The preparation method of the two-component catalyst provided in the present application adopts a simple catalyst preparation method such as urea precipitation method, vacuum impregnation method and coprecipitation method, which is suitable for large-scale industrial scale-up. After the reaction of catalyzing sugar conversion to 1,2-propylene glycol is completed, the two-component catalyst is filtered and separated and can be directly used in the next reaction.

[0086] 2) The dual-component catalyst provided in the present application uses non-precious metal nickel as the core active component and uses a common and readily available carrier, so the catalyst is low in cost.

[0087] 3) Compared with the traditional petroleum-based route, the present application uses sugar compounds as raw materials to prepare 1,2-propylene glycol, which has the advantages of green raw material sources, high product added value, and good atom economy.

[0088] 4) The dual-component catalyst provided in the present application exhibits excellent catalytic activity, good stability and high selectivity for the target product in the reaction of catalyzing sugar conversion to 1,2-propylene glycol, and has good application prospects. It exhibits excellent catalytic activity and high selectivity for 1,2-propylene glycol for different sugar substrates, and has good substrate adaptability.

[0089] 5) In the two-component catalyst provided in the present application, the active component and the co-metal component can play a synergistic role. The co-metal component improves the catalytic performance of the active component by regulating the electronic structure, geometric structure, acid properties and other properties of the multi-active component. At the same time, the co-metal component itself also has the activity of elementary reaction steps such as retro-aldol condensation and hydrogenolysis, thereby further regulating the reaction selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 This is a TEM image of the two-component catalyst prepared in Example 1 of the present application, with a scale of 20 nm. DETAILED DESCRIPTION

[0091] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0092] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0093] The analysis method in the examples of this application is as follows:

[0094] The samples were analyzed by high performance liquid chromatography (Agilent HPLC 1100, differential refractive index detector, Rezex TM The reaction solution of sugar catalytic hydrogenolysis reaction was analyzed by ROA-OrganicAcid H+ column.

[0095] In the examples of this application, the sugar raw material conversion rate is calculated as follows:

[0096]

[0097] The product yield in the examples of the present application is calculated as follows:

[0098]

[0099] Among them, X 糖 is the sugar raw material conversion rate; X 产物 is the product yield.

[0100] Example 1

[0101] 20g of basic alumina, 1000g of deionized water, 22g of nickel nitrate, and 160g of urea were placed in a single-necked flask with a stirrer, and aged for 12h at 20°C and 600rpm. A quartz condenser was installed on the top of the single-necked flask, and the flask was heated to 90°C in an oil bath for 24h. After the mixture was cooled naturally, it was filtered, washed with deionized water, and the filter cake was placed in a 100°C oven for 16h to obtain a two-component catalyst precursor A. 0.7g of cobalt nitrate was dissolved in 12g of deionized water, and an equal volume was impregnated in the two-component catalyst precursor A at an absolute pressure of 0.6Pa, and the mixture was allowed to stand for 12h. The mixture was dried in an oven at 100°C for 16h to obtain a two-component catalyst precursor B. The two-component catalyst precursor B was calcined at 400°C for 24h and treated at 450°C for 4h in a hydrogen atmosphere to obtain a two-component catalyst.

[0102] The TEM image of the prepared dual-component catalyst is shown in Figure 1 As shown by Figure 1 It can be seen that the metal particle size is less than 2 nm, indicating that the metal components are highly dispersed on the carrier.

[0103] Example 2

[0104] 15g of magnesium aluminum spinel, 450g of deionized water, 18g of nickel acetate, and 75g of urea were placed in a single-necked flask with a stirrer, and aged for 8h at 20℃ and 600rpm. A quartz condenser was installed on the top of the single-necked flask, and the flask was heated to 95℃ in an oil bath for 36h. After the mixture was cooled naturally, it was filtered, washed with deionized water, and the filter cake was placed in an oven at 100℃ for 12h to obtain a two-component catalyst precursor A. 1.6g of cerium nitrate was dissolved in 250g of deionized water, 19.5g of the two-component catalyst precursor A was added, and an aqueous solution containing 2wt% sodium carbonate was added under vigorous stirring until the mixture had a pH of 7, aged at 35℃ for 30h, filtered, washed with deionized water, and the filter cake was placed in an oven at 100℃ for 10h to obtain a two-component catalyst precursor B. The dual-component catalyst precursor B was calcined at 400°C for 12 h and treated at 550°C for 14 h in a hydrogen atmosphere to obtain the dual-component catalyst.

[0105] Example 3

[0106] The catalyst preparation process of Example 3 is the same as that of Example 1, except that 0.7 g of cobalt nitrate is replaced by 0.45 g of cerium nitrate.

[0107] Example 4

[0108] The catalyst preparation process of Example 4 is the same as that of Example 1, except that 20 g of basic alumina is replaced by 25 g of zinc oxide.

[0109] Example 5

[0110] The catalyst preparation process of Example 5 is the same as that of Example 1, except that 22 g of nickel nitrate is replaced by 27 g of nickel sulfate, and 0.7 g of cobalt nitrate is replaced by 1.1 g of chloropalladic acid.

[0111] Example 6

[0112] The catalyst preparation process of Example 6 is the same as that of Example 1, except that the hydrogen atmosphere is replaced by a methane atmosphere, and the reduction temperature of 450°C is replaced by 550°C.

[0113] Example 7

[0114] The catalyst preparation process of Example 7 is the same as that of Example 1, except that 0.7 g of cobalt nitrate is replaced by 1.7 g of zirconium oxynitrate, and the catalyst calcination temperature of 400° C. is replaced by 600° C.

[0115] Example 8

[0116] The catalyst preparation process of Example 8 is the same as that of Example 2, except that 15 g of magnesium aluminum spinel is replaced by 21 g of magnesium oxide.

[0117] Example 9

[0118] The catalyst preparation process of Example 9 is the same as that of Example 2, except that 18 g of nickel acetate is replaced by 26 g of nickel oxalate, 75 g of urea is replaced by 125 g, and 2 wt % sodium carbonate solution is replaced by 1 wt % ammonia water.

[0119] Example 10

[0120] The catalyst preparation process of Example 10 is the same as that of Example 2, except that 1.6 g of cerium nitrate is replaced by 3.2 g of ruthenium chloride.

[0121] Comparative Example 1

[0122] 20g of basic alumina, 1000g of deionized water, 22g of nickel nitrate, and 160g of urea were placed in a single-necked flask with a stirrer, stirred vigorously and aged for 12h, a quartz condenser was installed on the top of the single-necked flask, and the flask was heated to 90°C in an oil bath for 24h. After the mixture was cooled naturally, it was filtered and washed with deionized water. The filter cake was placed in an oven at 100°C and dried for 16h to obtain a two-component catalyst precursor A. The two-component catalyst precursor A was calcined at 400°C for 24h and treated at 450°C for 4h in a hydrogen atmosphere to obtain a two-component catalyst.

[0123] Comparative Example 2

[0124] 0.7 g of cobalt nitrate was dissolved in 12 g of deionized water, and an equal volume was impregnated into 20 g of basic alumina at an absolute pressure of 0.6 Pa. The mixture was allowed to stand for 12 h. The mixture was dried in an oven at 100 °C for 16 h, calcined at 400 °C for 24 h, and treated at 450 °C for 4 h in a hydrogen atmosphere to obtain a dual-component catalyst.

[0125] Test Example 1

[0126] The catalytic performance of the two-component catalysts prepared in Examples 1 to 10 and Comparative Examples 1 to 2 in the glucose hydrogenolysis reaction was evaluated.

[0127] Weigh 2.0g of the two-component catalyst, 50.0g of deionized water, and 5.0g of glucose into a high-pressure reactor, seal the reactor, replace the reaction atmosphere with a certain pressure of hydrogen, stir at a rate of 500r / min, heat to 240°C, and the hydrogen pressure reaches 8.5MPa. After reacting for 2h, cool naturally to room temperature. The reaction liquid is analyzed by high-performance liquid chromatography. The test results are shown in Table 1.

[0128] Table 1 Catalytic performance test results of the two-component catalysts prepared in Examples 1 to 10 and Comparative Examples 1 to 2

[0129]

[0130] As shown in Table 1, Examples 1 to 10 all exhibited excellent catalytic activity and over 40% selectivity for 1,2-propylene glycol. In contrast, although the two-component catalyst in Comparative Example 1 can effectively convert glucose, the product is mainly sorbitol. The two-component catalyst in Comparative Example 2 has limited catalytic activity and cannot fully convert the substrate.

[0131] Test Example 2

[0132] The catalytic stability of the two-component catalyst prepared in Example 1 in the glucose hydrogenolysis reaction was evaluated.

[0133] Weigh 2.0g of the two-component catalyst, 50.0g of deionized water, and 5.0g of glucose into a high-pressure reactor, seal the reactor, replace the reaction atmosphere with a certain pressure of hydrogen, stir at a rate of 500r / min, heat to 240°C, and the hydrogen pressure reaches 8.5MPa. After reacting for 2h, cool naturally to room temperature. The reaction liquid is analyzed by high-performance liquid chromatography. After the reaction is completed, the two-component catalyst is separated by filtration and directly used for the next evaluation. The test results are shown in Table 2.

[0134] Table 2 Catalytic stability test results of the two-component catalyst prepared in Example 1

[0135]

[0136] As shown in Table 2, the catalytic performance and 1,2-propylene glycol yield of the two-component catalyst prepared in Example 1 were maintained at a high level in three consecutive catalytic glucose hydrogenolysis reactions, indicating that the two-component catalyst has good stability. The catalytic stability test results of the two-component catalysts prepared in Examples 2 to 10 are similar to those in Example 1.

[0137] Test Example 3

[0138] The catalytic performance of the two-component catalyst prepared in Example 1 in the hydrogenolysis reaction of different sugar substrates was evaluated.

[0139] Weigh 2.0g of the two-component catalyst, 100.0g of deionized water, and 8.0g of sugar into a high-pressure reactor, seal the reactor, replace the reaction atmosphere with a certain pressure of hydrogen, stir at a rate of 500r / min, heat to 220°C, and the hydrogen pressure reaches 8MPa. After reacting for 4h, cool naturally to room temperature. The reaction liquid is analyzed by high-performance liquid chromatography. The test results are shown in Table 3.

[0140] Table 3 Test results of catalytic performance of the two-component catalyst prepared in Example 1 on different sugar substrates

[0141]

[0142] As shown in Table 3, the two-component catalyst prepared in Example 1 showed excellent catalytic activity and high 1,2-propylene glycol selectivity for different sugar substrates, indicating that the two-component catalyst has good substrate adaptability. The catalytic performance test results of the two-component catalysts prepared in Examples 2 to 10 for different sugar substrates are similar to those in Example 1.

[0143] Unless otherwise specified, all numbers appearing in the specification and claims of this application, such as temperature and time, conversion rate, yield, etc., should not be understood as absolutely precise values. Due to the standard deviation of the measurement technology, the measured values ​​inevitably have certain experimental errors.

[0144] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a two-component catalyst, characterized in that: The following steps are involved: S1: introducing the active component into the alkaline support by urea precipitation method to obtain a two-component catalyst precursor A; S2: introducing the co-metal component into the dual-component catalyst precursor A by vacuum impregnation or co-precipitation to obtain a dual-component catalyst precursor B; S3: calcining the dual-component catalyst precursor B, reducing and activating it, to obtain the dual-component catalyst; The alkaline carrier is selected from at least one of alkaline silica gel, alkaline alumina, magnesium oxide, zinc oxide, and magnesium aluminum spinel; The active component includes nickel element; The auxiliary metal component is selected from at least one of transition metal elements and lanthanide elements; The transition metal element is selected from at least one of zirconium, ruthenium, cobalt, iron, platinum and palladium; The lanthanide element is selected from at least one of cerium and lanthanum.

2. The preparation method according to claim 1, characterized in that: The content of the active component in the two-component catalyst is 5 to 40 wt%; The content of the auxiliary metal component in the dual-component catalyst is 0.1-4 wt%.

3. The preparation method according to claim 1, characterized in that: In step S1, the steps of preparing the dual-component catalyst precursor A by urea precipitation method are: The alkaline carrier, water, nickel salt and urea are mixed, stirred and aged, and the obtained mixture is placed in a container with a reflux device, heat-insulated and dried I to obtain the dual-component catalyst precursor A.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the alkaline carrier, water, nickel salt and urea is alkaline carrier: water: nickel salt: urea = 1: 25-150: 0.06-2.4: 0.1-9.5; Preferably, the nickel salt is selected from at least one of nickel nitrate, nickel oxalate, nickel chloride, nickel acetate, nickel sulfate and nickel carbonate; Preferably, the stirring aging temperature is 15 to 25°C; The stirring speed of the stirring aging is 150 to 10000 rpm; The stirring aging time is 2 to 24 hours; Preferably, the temperature of the heat preservation treatment is 75-100°C; The heat preservation treatment time is 12 to 72 hours; Preferably, the temperature of the drying I is 80-150°C; The drying time I is 1 to 48 hours.

5. The preparation method according to claim 1, characterized in that: In step S2, the steps of preparing the dual-component catalyst precursor B by vacuum impregnation are: Dissolving a metal salt in water to obtain a metal salt solution, mixing the metal salt solution with a two-component catalyst precursor A, impregnating with equal volumes, and drying II to obtain the two-component catalyst precursor B; Preferably, the temperature of the equal volume impregnation is 15 to 25°C; The pressure of the equal volume impregnation is ≤10Pa; The equal volume immersion time is 2 to 24 hours; Preferably, the temperature of the drying II is 70-150°C; The drying time II is 1 to 48 hours.

6. The preparation method according to claim 1, characterized in that: In step S2, the steps of preparing the dual-component catalyst precursor B by coprecipitation method are: Dissolving a metal salt in water to obtain a metal salt solution, adding a two-component catalyst precursor A to obtain a mixture C; dissolving a precipitant in water to obtain a solution D; adding the solution D to the mixture C under stirring until the pH value is 6 to 8, aging, and drying III to obtain the two-component catalyst precursor B; Preferably, the mass ratio of the two-component catalyst precursor A to the auxiliary metal salt is 1:0.001-0.2; Preferably, the precipitant is selected from at least one of ammonia water, sodium carbonate, sodium bicarbonate, and ammonium carbonate; Preferably, the mass content of the precipitant in the solution D is 0.5 to 16 wt %; Preferably, the aging temperature is 20-75°C; The aging time is 2 to 36 hours; Preferably, the temperature of the drying III is 70-150°C; The drying time of III is 1 to 48 hours.

7. The preparation method according to claim 5 or 6, characterized in that: The auxiliary metal salt is selected from at least one of cerium nitrate, lanthanum nitrate, zirconium oxynitrate, ruthenium chloride, cobalt nitrate, iron nitrate, chloroplatinic acid and chloropalladic acid.

8. The preparation method according to claim 1, characterized in that: In step S3, The calcination temperature is 350-700°C; The calcination time is 2 to 48 hours; Preferably, the reducing gas for reduction activation is selected from at least one of hydrogen and methane; The reduction activation temperature is 200-600°C; The reduction activation time is 0.5 to 24 hours.

9. Use of a two-component catalyst prepared by the preparation method according to any one of claims 1 to 8 in catalyzing the conversion of sugar solution into 1,2-propylene glycol, characterized in that: The following steps are involved: The two-component catalyst, water and sugar are added into a reaction kettle, which is sealed and replaced with a hydrogen atmosphere to react and obtain a product.

10. The use according to claim 9, characterized in that: The mass ratio of the two-component catalyst, water and sugar is 1:20-5000:0.2-500; Preferably, the sugar is selected from at least one of monosaccharides, disaccharides and polysaccharides; Preferably, the monosaccharide is selected from at least one of glucose, fructose and xylose; Preferably, the disaccharide is selected from at least one of maltose, sucrose, lactose and cellobiose; Preferably, the polysaccharide is selected from at least one of fructooligosaccharide, xylooligosaccharide, starch, straw sugar, and nanocellulose; Preferably, the reaction pressure is 1.5 to 16 MPa; The reaction temperature is 190-250°C; The reaction time is 0.2 to 12 hours.